Secret des hommes, secret des dieux L'aventure humaine et spirituelle du film'Des hommes et des dieux'. - Quinson, Henry (Paris Presses de la Renaissance, 2011)
Monastic adviser for the film "Des hommes et des dieux," Henry Quinson recounts this astonishing and rare spiritual adventure. Set in 1996 and based on the events of a true story that took place during the struggle for power by different Islamic guerrilla groups and the government in Algeria. Caught in the middle are a group of French Roman Catholic Trappist Order of Cistercians of the Strict Observance operating the self-sufficient monastery of Tibhiirine in the Algerian highlands and helping the people in the nearby village. The monks have been largely left alone by the area guerrilla fighters but when their leader is killed he is replaced by an even more brutal leader and the threat to their existence is imminent. They must decide to stay or go.
Keywords: Notre Dame de l'Atlas (Monastery : Tibehirine, Algeria); Des hommes et des dieux (Motion picture : 2010); Christian martyrs -- Algeria&delete& -- Tibehirine; Monastic and religious life -- Algeria -- Tibehirine -- History -- 20th century; Terrorism -- Algeria -- Tibehirine -- History -- 20th century; Tibehirine (Algeria) -- Church history -- 20th century